Of Women and Children. Bad Mothers as Rough Heroes - Vallorani, Nicoletta (E|C, 2020)
I want to borrow Reitz’s definition – global detective fiction – and some of her basic assumptions to reflect on the status of female characters as heroes in some current crime narratives, both literary and visual, and to analyse some “revised versions” of a specific aspect of femininity that used to be agreed upon, at least in patriarchal cultures. I want to speak of mothers and of their complex relation with their children: though my primary focus is on femininity, my argument implies a degree of reciprocity that makes it impossible to isolate one profile from the other. The discourse on mothers and children has deep implications for power, culture, representation, tradition, oppression and the desire to break free from several deeply-set social expectations.